Tailored inclusion of semiconductor nanoparticles in nanoporous polystyrene-block-polymethyl methacrylate thin films. (1st December 2020) - Malafronte, Anna; Emendato, Alessandro; Auriemma, Finizia; Sasso, Carmen; Laus, Michele; Murataj, Irdi; Lupi, Federico Ferrarese; De Rosa, Claudio
Abstract: Nanoporous/nanocomposite thin films with controlled morphology at nanoscale were prepared onto transparent and conductive indium tin oxide (ITO) supports by exploiting the self-assembly of a lamellar polystyrene- b -poly(methyl methacrylate) (PS- b -PMMA) block copolymer (BCP). A perpendicular orientation of PS and PMMA lamellar nanodomains was achieved by grafting a random PS- r -PMMA copolymer to the ITO supports and successive thermal annealing. Stable and reproducible nanoporous morphologies, characterized by PS lamellar nanodomains of width equal to ≈20 nm alternating to nanochannels of width equal to ≈8 nm, were obtained by irradiating the samples with an appropriate UV-C dose able to fix the relative arrangement of PS domains through activation of cross-linking reactions and selective removal of PMMA blocks. Nanoporous hybrid composites with a stable morphology were obtained either by applying the UV irradiation protocol to BCP nanocomposites characterized by selective inclusion of zinc oxide (ZnO) nanoparticles (NPs) in the PS domains (nanocomposite first/nanopores after) or by selective infiltration of cadmium selenide (CdSe) NPs in the nanochannels left free by PMMA removal through UV irradiation (nanopores first/nanocomposite after), demonstrating the strenght of the approach. Graphical abstract: Image 1 Highlights: Control of morphology at nanometer scale of block-copolymers thin films. Fabrication of block copolymers-based nanoporous nanocomposite thin films. Selective inclusion of semiconductive nanoparticles in block-copolymers.